A mixed user interface for a statistical system - Yoshikazu Yamamoto; Junji Nakano; Takeshi Fujiwara; Ikunori Kobayashi (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
A user interface is one of the most important factor's for deciding the usefulness of a statistical system. Nowadays, a graphical user interface (GUI) is popular because it is easy and intuitive to use. A character user interface (CUI) is, however, still important for using full abilities of the system by writing statistical programs in order to perform complicated statistical analyses which have not been realized in the system. We propose a mixed user interface for utilizing a GUI and a CUI alternatively and seamlessly, and consider its required characteristics. We also explain an implementation of the mixed user interface of the statistical system Jasp (Java based statistical processor), which is written in the Java language and adopts many recently developed computer technologies.
urn:nbn:de:kobv:11-10050516
Keywords: 330; Character user interface; Graphical user interface; History of a data analysis; Object-oriented approach